THE KINEMATICS OF USAIN BOLT’S MAXIMAL SPRINT VELOCITY (Kinesiology, 2018)
This study investigated the maximal sprint velocity kinematics of the fastest 100 m sprinter, Usain Bolt. Two high-speed video cameras recorded kinematics from 60 to 90 m during the men 100 m final at the World Challenge in Zagreb, Croatia. Despite a relatively slow reaction time (194 ms), Bolt won in 9.85 s (mean velocity: 10.15 m/s). His fastest 20-m section velocity was 12.14 m/s, reached between 70 to 90 m, and used a 2.70-m long stride and 4.36 strides/s frequency. At maximal velocity, his contact and flight times were 86 and 145 ms, and vertical ground reaction force equal to 4.2 times body weight (3932 N). The braking and propulsion phase represented 37 and 63% of ground contact, with his centre of mass exhibiting minor reductions in horizontal velocity (2.7%) and minimal vertical displacement (4.9 cm). Bolt's maximal sprint velocity and international dominance stem from advantageous anthropometrical characteristics, coordinated motor abilities, power generation capacities, and effective technique. This study confirms that his maximal velocity is achieved using a relatively long stride, minimal braking phase, high vertical ground reaction force, and minimal vertical displacement. This study is the first in-depth biomechanical analysis with segmental reconstruction of Bolt's maximal sprinting velocity.Keywords: 100 m sprint; athletics; biomechanics; sport performance; sprint running